Cognitive conceptual principle in foreign language teaching (Journal of Oriental Studies, 2016)
Cognitive lingua-cultural approach is quite different from traditional methods of teaching principles. Here we do not stop on a lexical level of words but comprehend the notions through various concept types and structures. Adopting this approach, which is a direction of Cognitive linguistics, we will write about its language features and its basic components. Cognitive Linguistics is a new approach to the study of language which views linguistic knowledge as part of general cognition and thinking; linguistic behavior is not separated from other general cognitive abilities which allow mental processes of reasoning, memory, attention or learning, but understood as an integral part of it. It emerged in the late seventies and early eighties, especially through the work of George Lakoff, one of the founders of generative linguistics.
Keywords: concept; conceptoshpere; world picture; cognition